The Influence of Working Capital Management on Business Sustainability in Small and Medium Enterprises - Rafi Akbar Nugraha; Nadia Maharani Putri (Economics Note, 2026)
Small and medium enterprises (SMEs) play a significant role in economic growth, employment generation, and regional development. Despite their contribution, many SMEs experience challenges in maintaining business sustainability due to inefficient financial management, particularly in managing working capital. This study aims to examine the influence of working capital management on business sustainability among SMEs in Indonesia. A quantitative explanatory research design was employed using a survey of 156 SME owners and managers selected through purposive sampling. Primary data were collected using a structured questionnaire based on a five-point Likert scale. Working capital management was measured through cash management, inventory management, accounts receivable management, accounts payable management, and liquidity management, while business sustainability was assessed through indicators of financial resilience, operational continuity, business growth, market competitiveness, and long-term viability. The data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and simple linear regression with IBM SPSS Statistics 27. The findings indicate that working capital management has a positive and statistically significant effect on business sustainability. SMEs with effective working capital practices demonstrate greater financial stability, improved operational efficiency, and stronger capacity to maintain business continuity in dynamic market conditions. The study highlights the importance of strengthening financial management capabilities among SME owners to enhance long-term business performance and sustainability. These findings contribute to the growing literature on SME financial management by providing empirical evidence from the Indonesian context and offer practical implications for business owners, financial institutions, and policymakers in designing programs that support sustainable SME development.